Comparison of traditional and advanced resistance training paradigms on muscle hypertrophy in trained individuals: a systematic review and meta-analysis - Fonseca, P. A.; Ide, B. N.; Oranchuk, D. J.; Marocolo, M.; Simim, M. A.; Roberts, M. D.; Mota, G. R. (Translational Sports Medicine, 2023)
Trained individuals may require variations in training stimuli and advanced resistance training paradigms (ADV) to increase skeletal muscle hypertrophy. However, no meta-analysis has examined how ADV versus traditional (TRAD) approaches may differentially affect hypertrophic outcomes in trained populations. The aim of this review was to determine whether the skeletal muscle hypertrophy responses induced by TRAD differed from ADV in resistance-trained individuals. Furthermore, we sought to examine potential effects of dietary factors, participants` training status, and training loads. We searched for peer-reviewed, randomized controlled trials (published in English) conducted in healthy resistance-trained adults performing a period of TRAD and ADV with pre-to-post measurement(s) of muscle hypertrophy in PubMed, Web of Science, SPORTDiscus, and MEDLINE databases up to October 2022. A formal meta-analysis was conducted in Revman5, and risk of bias was assessed by ROB2. Ten studies met the inclusion criteria. Results indicated no difference between ADV and TRAD for muscle thickness (SMD = 0.05, 95% CI: -0.20 0.29, = 0.70), lean mass (SMD = -0.01, 95% CI: -0.26 0.23, = 0.92), muscle cross-sectional area (SMD = -0.07, 95% CI: -0.36 0.22, = 0.64), or all measurements analyzed together (SMD = -0.00, 95% CI: -0.15 0.14, = 0.95). No heterogeneity or inconsistencies were observed; however, unclear risk of bias was present in most of the studies. Short-term ADV does not induce superior skeletal muscle hypertrophy responses when compared with TRAD in trained individuals. This review was not previously registered.